Forage potential and silage quality of four varieties of saccharine sorghum - Orrico Junior, Marco Antonio Previdelli; Retore, Marciana; Manarelli, Débora Maurício; Souza, Fernanda Barboza de; Ledesma, Luana Liz Medina; Orrico, Ana Carolina Amorim (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate four cultivars of saccharine sorghum (Sorghum bicolor) regarding productivity, chemical composition of plant parts, and quality of the ensiling process. The tested varieties of saccharine sorghum were BRS 506, BRS 508, BRS 509, and BRS 511. The experiment was divided into two trials, which assessed: production, morphological composition, and nutritional quality of the saccharine varieties; and fermentation quality and nutritional value of the silage produced from the saccharine varieties. Of the tested varieties, BRS 509 and BRS 511 showed the highest total dry matter (DM) production. The BRS 508 variety presented the highest in vitro digestibility of the whole plant (70.65% DM). During ensiling, the BRS 509 variety showed the lowest DM loss (8.87%). The highest effluent production was observed for BRS 506 and BRS 508, with yields of 521.87 and 393.16 kg Mg‑1 ensiled DM, respectively. The BRS 511 variety is the most recommended because of the best results for plant production and nutritional quality. Regarding the ensiling process, BRS 509 presents the lowest fermentation losses and the highest nutritional value of silage.
Keywords: Sorghum bicolor; forage system; nutritional value; roughage; ruminant